Physical and chemical evaluation of extracted peanut oil (arachis hypogaea) (Research, Society and Development, 2021)
The oil extracted from the peanut seed has beneficial health properties as it is antioxidant, anti-inflammatory and prevents coronary heart disease. Despite this quality, improper processing and storage can cause degradation such as lipid oxidation due to its polyunsaturation. The work aimed to evaluate the physical and chemical characteristics of oil extracted from peanuts and commercial peanut oil. The extraction and analysis of the acidity index, % of Free Fatty Acids (AGL), peroxide index and oil iodine index were carried out in the laboratories of the Federal Institute of Piauí (IFPI), Teresina Central campus. The peanut oil was extracted with hexane, using the Bligh & Dyer method and the commercialized peanut oil was obtained in the local market. The oil extracted by the two methods had the oil-chemical indexes within that recommended by the legislation while the industrialized oil was above the standard. The most efficient extraction method was Bligh & Dyer, demonstrating that the extraction method interferes with the physicochemical characteristics and oil yield.